Polarizing film and method for producing the same
By adjusting the proportion and distribution of boric acid and boron-containing compounds, combined with uniaxial stretching and impregnation treatment, the problems of insufficient polarization performance and low transmittance of polarization films in the prior art are solved, and high polarization performance and high transmittance are achieved. Polarizing film meets the high-refining requirements of electronic equipment.
Patent Information
- Application Number
- CN202180020786.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-13
- Filing Date
- 2021-03-11
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-03-11
AI Technical Summary
It is difficult for the prior art to achieve a polarizing film with high polarization performance and high transmittance at the same time, and the tensile properties of the high polymerization PVA film are reduced. The concentration in boric acid treatment is not strictly managed, resulting in insufficient decomposition of iodine-based pigments, affecting polarization performance.
By adjusting the amount and proportion of boric acid and boron-containing compounds in the cross-linking of PVA molecular chain, we ensure that the concentration of boron-containing compounds near the surface of the polarizing film is high. The combination of monoboric acid and boric acid is used, combined with uniaxial stretching and impregnation treatment, and prepared A polarizing film with high polarization performance and high transmittance.
A polarizing film with high polarization performance and high transmittance is achieved, which improves the heat resistance and durability of the polarizing film, and meets the high-refining requirements of electronic equipment.
Smart Images

Figure CN115244440B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing film and a method for producing the same. Background Art
[0002] Polarizing plates, which have the functions of transmitting and shielding light, and liquid crystals that change the polarization state of light are the basic components of liquid crystal displays (LCDs). In order to prevent the fading and shrinkage of the polarizing film, most polarizing plates have a structure in which a protective film such as a triacetylcellulose (TAC) film is attached to the surface of the polarizing film. The mainstream polarizing film constituting the polarizing plate is a substrate obtained by uniaxially stretching a polyvinyl alcohol film (hereinafter sometimes referred to as "polyvinyl alcohol" as "PVA") and adsorbing an iodine-based dye (I3 - 、I5 - A polarizing film obtained by
[0003] LCDs are widely used in small devices such as calculators and watches, smartphones, laptops, liquid crystal displays, liquid crystal color projectors, liquid crystal televisions, car navigation systems, and indoor and outdoor measurement equipment. In recent years, 4K and 8K LCDs have been put into practical use, and the high-precision of LCDs has been progressing. On the other hand, the problem of reduced light extraction efficiency caused by the reduction in aperture ratio has been formed. Based on this situation, in order to compensate for the reduced light extraction efficiency caused by the reduction in aperture ratio, a polarizing film with high polarization performance and high transmittance is required.
[0004] As a method for obtaining a polarizing film with high polarization performance, a method using PVA with a high degree of polymerization is known (for example, Patent Document 1). However, when PVA with a high degree of polymerization is used, the stretchability of the PVA film is reduced, so there is a problem that the yield of the polarizing film is reduced.
[0005] In addition, there is also a known method of treating a polarizing film with a reducing agent to decompose unnecessary iodine-based dyes (eg, Patent Document 2). However, if the concentration of the reducing agent is not strictly controlled, the iodine-based dyes decompose more than necessary, making industrial implementation difficult.
[0006] In recent years, a method of using an aqueous solution of boric acid to crosslink the PVA molecular chains in the polarizing film has been developed. For example, Patent Document 3 describes that after uniaxial stretching, the PVA film is immersed in an aqueous solution (fixing treatment bath) containing boric acid such as methylboric acid and 1,4-butanediboric acid and potassium iodide, thereby obtaining a polarizing film with excellent moisture and heat resistance. In addition, Patent Documents 4 and 5 describe that the PVA film is treated with monoboric acid to impart hydrophobicity, thereby obtaining a polarizing film with excellent moisture and heat resistance, and a polarizing film with high polarization performance and low shrinkage force under high temperature.
[0007] However, the polarizing films described in Patent Documents 3 to 5 still have insufficient polarization performance in order to meet the demand for higher definition of electronic devices.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 01-084203
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 2013-156621
[0012] Patent Document 3: WO2018 / 021274
[0013] Patent Document 4: KR10-2015-0052777
[0014] Patent document 5: WO2019 / 146677. Summary of the invention
[0015] Problems to be solved by the invention
[0016] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a polarizing film having high polarization performance and high transmittance, and a method for producing the same.
[0017] Solutions to Solve Problems
[0018] The inventors of the present invention have conducted intensive research and found that in order to obtain a polarizing film with high polarization performance and high transmittance, it is important to adjust the amount and ratio of boric acid (C) and boron-containing compound (B) used in the cross-linking of PVA molecular chains in the polarizing film to an appropriate range, and to have a larger amount of boron-containing compound (B) present near the surface of the polarizing film.
[0019] The present invention is
[0020] [1] A polarizing film comprising PVA (A), a boron-containing compound (B) selected from the group consisting of monoboric acid represented by the following formula (I) and a compound that can be converted into the monoboric acid in the presence of water, and boric acid (C), wherein the boron content (b) derived from the boron-containing compound (B) is t ) is 0.3 to 2.0 mass %, the total boron content (T) is 3.0 to 7.0 mass %, and (b t ) relative to (T) (b t / T) is 0.10 to 0.30, and the concentration of boron element (b) derived from the boron-containing compound (B) in the range from at least one surface to the inside to 7.5% of the total thickness (hereinafter, this range may be referred to as the surface portion) o ) is 2.2~10.0atomic%
[0021]
Chemical formula 1
[0022]
[0023] In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 Connected to the boronic acid group by a boron-carbon bond;
[0024] [2] The polarizing film according to [1], wherein the concentration of the boron element (b) derived from the boron-containing compound (B) in a range from the center of the polarizing film to 7.5% of the total thickness (hereinafter, this range may be referred to as the center portion) is i ) is 0.5 to 2.0 atomic %, and the boron element concentration (c i ) is 3.5~8.0atoms%;
[0025] [3] The polarizing film according to [1] or [2], wherein the concentration of the boron element (b) derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside is 7.5% relative to the total thickness. i ) relative to the boron concentration (c i ) ratio (b i / c i ) is 0.01~0.25;
[0026] [4] The polarizing film according to any one of [1] to [3], wherein the concentration of the boron element (c) derived from the boric acid (C) in the range from at least one surface of the polarizing film to the inner side thereof is 7.5% relative to the total thickness. o ) is 3.3~7.8atomic%;
[0027] [5] The polarizing film according to any one of [1] to [4], wherein the concentration of the boron element (b) derived from the boron-containing compound (B) in the range from at least one surface of the polarizing film to the inner side thereof is 7.5% relative to the total thickness. o ) is greater than the boron element concentration (b) derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside to 7.5% relative to the total thickness. i )high;
[0028] [6] The polarizing film according to any one of [1] to [5], wherein the concentration of the boron element (c) derived from the boric acid (C) in the range from at least one surface of the polarizing film to the inner side thereof is 7.5% relative to the total thickness. o ) is greater than the boron element concentration (c) derived from the boric acid (C) in the range from the center of the polarizing film to the outside to 7.5% relative to the total thickness.i )Low;
[0029] [7] The polarizing film according to any one of [1] to [6], wherein R 1 It is a saturated aliphatic group;
[0030] [8] The polarizing film according to any one of [1] to [7], wherein R 1 is a straight-chain aliphatic hydrocarbon group;
[0031] [9] The polarizing film according to any one of [1] to [8], wherein R 1 The number of carbon atoms is 2 to 5;
[0032]
[10] The polarizing film according to any one of [1] to [9], wherein the transmittance is 42% or more when the degree of polarization is 99.9% or more;
[0033]
[11] A method for producing a polarizing film according to any one of [1] to
[10] , comprising a dyeing treatment of a polyvinyl alcohol film with a dichroic dye, and a stretching treatment of the film by uniaxially stretching the film, wherein the film is immersed in an aqueous solution containing a boric acid crosslinking agent and then immersed in an aqueous solution containing 1.5 to 5.0 mass % of a boron-containing compound (B) at a temperature of 35 to 80°C.
[0034] Effects of the Invention
[0035] The polarizing film of the present invention is a polarizing film having high polarization performance and high transmittance. According to the production method of the present invention, such a polarizing film can be easily produced.
[0036] Brief description of the attached figure
[0037]
Figure 1
[0038] This is a schematic diagram showing a cross section in the thickness direction of the polarizing film of the present invention.
[0039]
Figure 2
[0040] The polarizing film obtained in Example 1 1 H-NMR spectrum. DETAILED DESCRIPTION
[0041] <Polarizing film>
[0042] The polarizing film of the present invention comprises PVA (A), a boron-containing compound (B) selected from the group consisting of monoboric acid represented by the following formula (I) and a compound that can be converted into the monoboric acid in the presence of water, and boric acid (C), wherein the boron content (b) derived from the boron-containing compound (B) is t) is 0.3 to 2.0 mass %, the total boron content (T) is 3.0 to 7.0 mass %, and (b t ) relative to (T) (b t / T) is 0.10 to 0.30, and the boron element concentration (b) derived from the boron-containing compound (B) in the range of 7.5% from at least one surface to the inside with respect to the entire thickness o ) is 2.2~10.0atomic%
[0043]
Chemical formula 2
[0044]
[0045] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 Connected to the boronic acid group by a boron-carbon bond. ]
[0046] Thus, by comparing the total boron content (T) in the polarizing film, the boron content (b t ) and their ratio are set to a specific range, and the boron element concentration (b o ) is set to a specific range, a polarizing film with high polarization performance and high transmittance can be obtained. The reason for this is that the presence of a large amount of the boron-containing compound (B) on the surface of the polarizing film can suppress the dissolution of boric acid (C) from the inside. Therefore, it is believed that the reason is that the relaxation of the orientation of PVA in the central part of the polarizing film can be suppressed, and at the same time, the unnecessary iodine-based pigment on the surface of the polarizing film can be removed by the boron-containing compound (B).
[0047] Generally, when a PVA film cross-linked with boric acid is immersed in an aqueous solution of a boron-containing compound (B), a reaction of replacing boric acid (C) with a boron-containing compound (B) is carried out from the surface of the PVA film. Here, in order to have a large amount of boron-containing compound (B) on the surface of the PVA film, it is important to accelerate the replacement reaction of boric acid (C) and boron-containing compound (B) on the surface of the PVA film by immersing the PVA film in an aqueous solution of a boron-containing compound (B) at a higher concentration and a higher temperature as described later. When the concentration of the boron-containing compound (B) is low, the dissolution of boric acid (C) takes precedence over the adsorption of the boron-containing compound (B). In this case, even the boric acid (C) in the central part of the PVA film is dissolved, and the orientation of the PVA is relaxed, so it is difficult to obtain a polarizing film with high polarization performance and high transmittance. In addition, there is also a concern that the rigidity of the polarizing film is reduced and wrinkles are generated. When the aqueous solution of the boron-containing compound (B) is low, boric acid (C) is difficult to dissolve, so the boron-containing compound (B) is not adsorbed. In this case, since the polarization performance improvement effect brought about by the addition of the boron-containing compound (B) is insufficient, a polarizing film with high polarization performance and high transmittance cannot be obtained. On the other hand, when the PVA film cross-linked with boric acid is immersed in an aqueous solution of a boron-containing compound (B) at a relatively high concentration and high temperature, the above-mentioned substitution reaction proceeds rapidly on the surface of the PVA film. As a result, it is believed that the relaxation of the orientation of the PVA in the central part of the PVA film can be suppressed, and at the same time, the unnecessary iodine-based pigment on the surface of the PVA film is removed by the boron-containing compound (B), so that a polarizing film with high polarization performance and high transmittance can be obtained.
[0048] The boron-containing compound (B) in the polarizing film of the present invention is at least one selected from the group consisting of the monoboric acid represented by the above formula (I) and a compound that can be converted into the monoboric acid in the presence of water. 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 It is connected to the boronic acid group by a boron-carbon bond.
[0049] Monoboric acid is a compound represented by the above formula (I), and has one organic boronic acid group [-B(OH)2] in one molecule. The boronic acid group has a structure in which a boron atom bonded to two hydroxyl groups is bonded to a carbon atom. In the compound represented by formula (I), R 1 It is connected to the boronic acid group by a boron-carbon bond. In boric acid [B(OH)3], the boron atom is bonded to three hydroxyl groups, whereas the boronic acid group is different in that it has a boron-carbon bond. As a boron-containing group that can be converted into a boronic acid group in the presence of water, the borate ester group described below can be cited as a representative group, but it is not limited thereto.
[0050] The hydroxyl group in the boronic acid group contained in monoboric acid can form an ester with an alcohol in the same manner as the hydroxyl group in boric acid. The following formula (II) is one molecule of alcohol (R 2Here, when the boric acid group is bonded to the hydroxyl group of PVA (A), R in formula (II) 2 It is a PVA chain to which a carbon-containing group is bonded via a boron atom.
[0051]
Chemical formula 3
[0052]
[0053] The following formula (III) is two molecules of alcohol (R 2 Here, when the boric acid group is bonded to the hydroxyl group of PVA, the two R 2 All are PVA chains.
[0054]
Chemical formula 4
[0055]
[0056] Monoboric acid has two hydroxyl groups that can react with the hydroxyl groups of PVA to form esters, causing the PVA chains to be moderately cross-linked. The reason is unclear, but it is believed that due to the cross-linking, the orientation of PVA is high, or the unnecessary iodine-based pigment is destabilized and reduced, thereby improving the polarization performance of the polarizing film, thereby forming a polarizing film with high polarization performance and high transmittance.
[0057] In formula (I), R 1 It is a monovalent aliphatic group having 1 to 20 carbon atoms. 1 The length of R is appropriate to control the solubility of the boron-containing compound (B) in water and the reactivity with the hydroxyl group of PVA. From the viewpoint of obtaining a polarizing film with good adsorption to the polarizing film and excellent optical properties, R 1 The number of carbon atoms in R is preferably 10 or less, more preferably 6 or less, and further preferably 5 or less. On the other hand, from the viewpoint of particularly excellent balance between the optical properties and the shrinkage force of the polarizing film, R 1 The number of carbon atoms in is preferably 2 or more, more preferably 3 or more.
[0058] In formula (I), as long as R 1 is a monovalent aliphatic group, and R 1 It can be connected to the boric acid group by a boron-carbon bond. 1 It can be a saturated aliphatic group or an unsaturated aliphatic group, and the former is preferred. 1 A saturated aliphatic group is used, thereby suppressing the coloring of the obtained polarizing film and improving the durability. 1It is a saturated aliphatic group, which improves the orientation of the dichroic pigment and further improves the optical performance. It should be noted that the unsaturated aliphatic group refers to an aliphatic group having a structure containing a carbon-carbon double bond, a carbon-carbon triple bond, a carbon-oxygen double bond, a carbon-nitrogen double bond, a nitrogen-nitrogen double bond, a carbon-sulfur double bond, and a multi-bond structure with a bonding order of 2 or more, and the saturated aliphatic group refers to an aliphatic group having only a single bond structure. 1The monoboric acid which is a saturated aliphatic group may be exemplified by methylboric acid, ethylboric acid, propylboric acid, butylboric acid, pentylboric acid, hexylboric acid, heptylboric acid, octylboric acid, nonylboric acid, decylboric acid, undecylboric acid, dodecylboric acid, tridecylboric acid, tetradecylboric acid, pentadecylboric acid, hexadecylboric acid, heptadecylboric acid, octadecylboric acid, nonadecylboric acid, eicosaneboric acid and isomers thereof; cyclopropylboric acid, cyclobutylboric acid, cyclopentylboric acid, cyclohexylboric acid, cycloheptylboric acid, cyclooctylboric acid, cyclononylboric acid, cyclodecylboric acid, cycloundecylboric acid, cyclododecylboric acid, cyclotridecylboric acid, cyclo tetradecylboric acid, cyclopentadecylboric acid, cyclohexadecylboric acid, cycloheptadecylboric acid, cyclooctadecylboric acid, cyclononadecylboric acid, cycloeicosaneboric acid and their isomers; 2-oxa-propylboric acid, 2-oxa-butylboric acid, 2-oxa-hexylboric acid, 2-oxa-heptylboric acid, 2-oxa-octylboric acid, 2-oxa-nonylboric acid, 2-oxa-decylboric acid, 2-oxa-undecylboric acid, 2-oxa-dodecylboric acid, 2-oxa-tridecylboric acid, 2-oxa-tetradecylboric acid, 2-oxa-pentadecylboric acid, 2-oxa-hexadecylboric acid, 2-oxa-heptadecylboric acid, 2-oxa- 2-Aza-octadecylboric acid, 2-Aza-nonadecanylboric acid, 2-Aza-eicosaneboric acid and their isomers; 2-Aza-propylboric acid, 2-Aza-butylboric acid, 2-Aza-hexylboric acid, 2-Aza-heptylboric acid, 2-Aza-octylboric acid, 2-Aza-nonylboric acid, 2-Aza-decylboric acid, 2-Aza-undecylboric acid, 2-Aza-dodecylboric acid, 2-Aza-tridecylboric acid, 2-Aza-tetradecylboric acid, 2-Aza-pentadecanylboric acid, 2-Aza-hexadecylboric acid, 2-Aza-heptadecylboric acid, 2-Aza-octadecylboric acid, 2-Aza-nonadecanylboric acid Boric acid, 2-aza-eicosaneboric acid and isomers thereof; 2-phospha-propylboric acid, 2-phospha-butylboric acid, 2-phospha-hexylboric acid, 2-phospha-heptylboric acid, 2-phospha-octylboric acid, 2-phospha-nonylboric acid, 2-phospha-decylboric acid, 2-phospha-undecylboric acid, 2-phospha-dodecylboric acid, 2-phospha-tridecylboric acid, 2-phospha-tetradecylboric acid, 2-phospha-pentadecylboric acid, 2-phospha-hexadecylboric acid, 2-phospha-heptadecylboric acid, 2-phospha-octadecylboric acid, 2-phospha-nonadecylboric acid, 2-phospha-eicosaneboric acid and isomers thereof;2-thia-propylboric acid, 2-thia-butylboric acid, 2-thia-hexylboric acid, 2-thia-heptylboric acid, 2-thia-octylboric acid, 2-thia-nonylboric acid, 2-thia-decylboric acid, 2-thia-undecylboric acid, 2-thia-dodecylboric acid, 2-thia-tridecylboric acid, 2-thia-tetradecylboric acid, 2-thia-pentadecylboric acid, 2-thia-hexadecylboric acid, 2-thia-heptadecylboric acid, 2-thia-octadecylboric acid, 2-thia-nonadecylboric acid, 2-thia-eicosaneboric acid and isomers thereof. In addition, as compounds that can be converted into the exemplified monoboric acid in the presence of water, salts of the monoboric acid and the like can be mentioned. ;
[0059] R 1 It may be an aliphatic hydrocarbon group, and may contain heteroatoms such as oxygen, nitrogen, sulfur, and halogen. 1 It is preferably an aliphatic hydrocarbon group containing no heteroatoms. As the aliphatic hydrocarbon group, it is preferably a straight-chain aliphatic hydrocarbon group without branches. As a result, the adsorption to the polarizing film becomes good and the effect of increasing the optical performance is improved. It should be noted that as R 1 The boric acid which is a straight-chain aliphatic hydrocarbon group specifically includes methylboric acid, ethylboric acid, n-propylboric acid, n-butylboric acid, n-pentylboric acid, n-hexylboric acid, n-heptylboric acid, n-octylboric acid, n-nonylboric acid, n-decylboric acid, n-undecylboric acid, n-dodecylboric acid, n-tridecylboric acid, n-tetradecylboric acid, n-pentadecylboric acid, n-hexadecylboric acid, n-heptadecylboric acid, n-octadecylboric acid, n-nonadecylboric acid, n-eicosylboric acid, etc. In addition, as a compound which can be converted into the exemplified boric acid in the presence of water, salts of the boric acid, etc. can be mentioned.
[0060] Specifically, as the monoboric acid represented by the above formula (I), ethylboric acid, n-propylboric acid, n-butylboric acid, and n-pentylboric acid are preferred, and n-propylboric acid and n-butylboric acid are more preferred. In addition, as compounds that can be converted into these exemplified boric acids in the presence of water, salts of the boric acids can be cited.
[0061] The boron content (b t ) needs to be 0.3 to 2.0 mass %. (b t ) is less than 0.3 mass %, since crosslinking by the boron-containing compound (B) is insufficient, a polarizing film having high polarization performance and high transmittance cannot be obtained. t ) is 0.5 mass % or more. On the other hand, (b t) exceeds 2.0 mass %, the reaction between the boron-containing compound (B) and PVA proceeds excessively, inhibiting the formation of iodine-based dyes, and a polarizing film with high polarization performance and high transmittance cannot be obtained. t ) is preferably 1.8 mass % or less, more preferably 1.6 mass % or less, further preferably 1.4 mass % or less, particularly preferably 1.3 mass % or less, and most preferably 1.2 mass % or less. The boron content (b) derived from the boron-containing compound (B) in the polarizing film t ) can be achieved through 1 The boron content (b) was obtained by combining H-NMR measurement with ICP emission analysis, specifically, by the method described in the Examples. t ) and the total boron content (T) described later can be measured using a polarizing film conditioned at 23° C. and 50% RH for 16 hours.
[0062] The total boron content (T) of the polarizing film needs to be 3.0 to 7.0% by mass. When the total boron content (T) in the polarizing film is less than 3.0% by mass, the number of crosslinking points becomes insufficient, the orientation of PVA is disordered, and a polarizing film with high polarization performance and high transmittance cannot be obtained. (T) is preferably 3.5% by mass or more, more preferably 4.1% by mass or more, and further preferably 4.2% by mass or more. On the other hand, when the total boron content (T) in the polarizing film exceeds 7.0% by mass, the polarization performance is reduced due to excessive adsorption of iodine-based pigments in the polarizing film. In addition, the PVA film is prone to breakage in the drying process and stretching process described later, and the productivity of the polarizing film is reduced. The total boron content (T) in the polarizing film is preferably 6.5% by mass or less, more preferably 5.5% by mass or less, further preferably 5.0% by mass or less, and particularly preferably 4.8% by mass or less. The total boron content (T) in the polarizing film can be obtained by ICP emission analysis, etc. Specifically, it can be obtained by the method described in the embodiment.
[0063] The boron content (b t The ratio of (mass %) to the total boron content (T) (mass %) (b t / T) needs to be 0.10 to 0.30. t When the ratio (b / T) is less than 0.10, the ratio of the crosslinking points derived from the boron-containing compound (B) in all the crosslinking points of PVA in the polarizing film is too low, so the effect of improving the polarization performance by the boron-containing compound (B) becomes insufficient. t / T) is preferably 0.12 or more, more preferably 0.15 or more. tWhen the ratio (b / T) exceeds 0.30, the ratio of the crosslinking points derived from the boron-containing compound (B) in all the crosslinking points of PVA in the polarizing film is too high, so that the formation of the iodine-based dye is sometimes suppressed, and a polarizing film with high polarization performance and high transmittance cannot be obtained. t / T) is preferably 0.27 or less, more preferably 0.25 or less, further preferably 0.23 or less, and particularly preferably 0.18 or less.
[0064] Figure 1 Schematic diagram showing a cross section in the thickness direction of the polarizing film of the present invention. Figure 1 The polarizing film is further described. From at least one surface 1 of the polarizing film to the inner side relative to the overall thickness t t The range of 7.5% or less (surface portion 2, thickness t of surface portion 2) o and the overall thickness of the polarizing film t t Satisfy "t o =t t ×0.075”) and the boron concentration (b o ) needs to be 2.2 to 10.0 atomic %. (b o ) is less than 2.2 atomic %, the effect of inhibiting the dissolution of boric acid from the surface of the polarizing film by the boron-containing compound (B) becomes insufficient, and the efficiency of improving the polarization performance becomes small, so that a polarizing film with high polarization performance and high transmittance cannot be obtained. (b o ) is preferably 2.4 atomic % or more, more preferably 2.8 atomic % or more. On the other hand, (b o When the content of boron-containing compound (B) exceeds 10.0 atomic %, there is no disadvantage in polarization performance, but precipitates of the boron-containing compound (B) are generated on the surface of the polarizing film, thereby reducing the productivity of the polarizing film. (b o ) is preferably 8 atomic % or less, more preferably 6 atomic % or less, further preferably 5 atomic % or less, and particularly preferably 4 atomic % or less. The boron element concentration (b) derived from the boron-containing compound (B) on the surface portion 2 on both sides of the polarizing film o ) is preferably within the above range.
[0065] Boron concentration (b o ) can be obtained using an X-ray photoelectron spectrometer with a gas cluster ion beam gun (GCIB XPS). Using GCIB XPS, etching and measurement are repeated to measure the concentration of boron derived from the boron-containing compound (B) at a certain interval from the surface of the polarizing film to the inside. And, the average value of the concentration of boron derived from the boron-containing compound (B) in the aforementioned range (surface portion 2) is set as the boron concentration (b o Specifically, it can be obtained by the method described in the examples described below. The boron element concentration (bi )、(c o ), and (c i ) also uses (b o ) is obtained in the same way.
[0066] From the center 3 of the polarizing film to the outside relative to the total thickness t t The range of 7.5% to 7.5% (the thickness t of the central portion 4 and the central portion 4) i and the overall thickness of the polarizing film t t Satisfy "t i =t t ×0.15”) and the boron concentration (b i ) is preferably 0.5 to 2.0 atomic %. In addition, the boron element concentration (c i ) is also preferably 3.5 to 8.0 atomic %. Furthermore, (b) in the aforementioned range (central portion 4) is more preferably i ) is 0.5 to 2.0 atomic %, and (c i ) is 3.5 to 8.0 atomic %.
[0067] The concentration of the boron element (b i When the content exceeds 2.0 atomic %, the boron-containing compound (B) present in the polarizing film becomes excessive, which may inhibit the formation of iodine-based dyes, which is not preferred. (b i ) is more preferably 1.8 atomic % or less, further preferably 1.5 atomic % or less, and particularly preferably 1.3 atomic % or less. On the other hand, (b i When the content of boron-containing compound (B) is less than 0.5 atomic %, the amount of boron-containing compound (B) in the polarizing film is insufficient, and the effect of improving polarization performance may be insufficient. i ) is more preferably 0.8 atomic % or more, and further preferably 0.9 atomic % or more.
[0068] The boron element concentration (c i ) exceeds 8.0 atomic %, since adsorption of the boron-containing compound (B) into the polarizing film is suppressed, which is not preferable. (c i ) is more preferably 7.0 atomic % or less, and further preferably 6.0 atomic % or less. On the other hand, (c i ) is less than 3.5 atomic %, the number of crosslinking points becomes insufficient, and there is a concern that the PVA orientation state cannot be maintained and a polarizing film with high polarization performance cannot be obtained. (c i ) is more preferably 4.0 atomic % or more, further preferably 4.5 atomic % or more, and particularly preferably 5.0 atomic % or more.
[0069] The concentration of the boron element (b i ) relative to the boron concentration (c i ) ratio (b i / c i ) is preferably 0.01 to 0.25. i / c i ) is less than 0.01, the ratio of the boron-containing compound (B) to the boric acid (C) in the polarizing film is low, so there is a concern that the effect of improving the polarization performance by adding the boron-containing compound (B) is insufficient. i / c i ) is more preferably 0.08 or more, further preferably 0.10 or more, particularly preferably 0.12 or more, and most preferably 0.15 or more. i / c i ) exceeds 0.25, since the formation of iodine-based pigments is inhibited, which is not preferred. i / c i ) is more preferably less than 0.20.
[0070] From at least one surface 1 of the polarizing film to the inner side relative to the overall thickness t t The boron element concentration (c o ) is preferably 3.3 to 7.8 atomic %. (c o ) is less than 3.3 atomic %, boric acid often dissolves excessively from the polarizing film. When boric acid dissolves excessively, a polarizing film with high polarization performance may not be obtained. (c o ) is more preferably 4.0 atomic % or more, and further preferably 4.5 atomic % or more. On the other hand, (c o ) When the content exceeds 7.8 atomic %, there is a concern that scratches may be easily introduced on the surface 1 of the polarizing film, or there is a concern that the adsorption of the boron-containing compound (B) to the PVA film may be inhibited. (c o ) is more preferably 7.0 atomic % or less, further preferably 6.5 atomic % or less, particularly preferably 5.5 atomic % or less, and most preferably 4.8 atomic % or less. The boron element concentration (c o ) is more preferably within the above range.
[0071] From at least one surface 1 of the polarizing film to the inner side relative to the overall thickness t t The boron element concentration (b o ) is preferably greater than the thickness t from the center 3 of the polarizing film to the outside relative to the overall thickness tt The concentration of the boron element (b) derived from the boron-containing compound (B) in the range of up to 7.5% (central portion 4) is i )High. (b o ) relative to (b i ) ratio (b o / b i ) is less than 1, the effect of inhibiting the dissolution of boric acid brought about by the boron-containing compound (B) on the surface of the polarizing film becomes insufficient, and the effect of improving the polarization performance becomes small. Therefore, there is a concern that a polarizing film with high polarization performance and high transmittance cannot be obtained, or there is a concern that the boron-containing compound (B) present in the polarizing film becomes excessive, thereby inhibiting the formation of iodine-based pigments. (b o ) relative to (b i ) ratio (b o / b i ) is more preferably 1.1 or more, further preferably 1.5 or more, particularly preferably 2.0 or more, and most preferably 2.5 or more. o / b i ) is preferably 8.0 or less, and more preferably 7.0 or less. From the perspective of obtaining a polarizing film with extremely high polarization performance and transmittance and further improving the productivity of the polarizing film, the ratio (b o / b i ) is preferably 6.0 or less, more preferably 5.0 or less, further preferably 4.5 or less, and particularly preferably 4.0 or less. The boron element concentration (b) derived from the boron-containing compound (B) on the surface portion 2 on both sides of the polarizing film o ) is more preferably higher than the boron element concentration (b i )high.
[0072] From at least one surface 1 of the polarizing film to the inner side relative to the overall thickness t t The boron element concentration (c o ) is preferably greater than the thickness from the center of the polarizing film to the outside relative to the overall thickness t t The boron element concentration (c i )Low. (c o ) relative to (c i ) ratio (c o / c i ) is 1 or more, there is a concern that the surface 1 of the polarizing film may be easily scratched, or the adsorption of the boron-containing compound (B) onto the PVA film may be inhibited, or the number of crosslinking points may become insufficient, and the PVA orientation state may not be maintained, thereby failing to obtain a polarizing film with high polarization performance. (c o ) relative to (c i) ratio (c o / c i ) is more preferably 0.99 or less, further preferably 0.95 or less, particularly preferably 0.90 or less, and most preferably 0.85 or less. On the other hand, from the perspective of obtaining a polarizing film with higher polarization performance and facilitating the adsorption of the boron-containing compound (B) into the interior of the polarizing film, the ratio (c o / c i ) is 0.5 or more. More preferably, the boron element concentration (c o ) is greater than the boron element concentration (c i )Low.
[0073] The thickness of the polarizing film is preferably 5 to 60 μm. When the thickness is less than 5 μm, it is easy to break due to stretching during manufacturing, and there is a concern about reduced productivity. The thickness is more preferably 10 μm or more. On the other hand, when the thickness exceeds 60 μm, there is a concern that the performance required of the polarizing plate, such as thin film and light weight, cannot be met. Therefore, the thickness is more preferably 45 μm or less, more preferably 30 μm or less, and particularly preferably 25 μm or less.
[0074] <PVA(A)>
[0075] The PVA (A) in the present invention is a polymer having a vinyl alcohol unit (-CH2-CH(OH)-) as a main structural unit.
[0076] The degree of polymerization of PVA (A) contained in the polarizing film of the present invention is preferably in the range of 1500 to 6000, more preferably in the range of 1800 to 5000, and further preferably in the range of 2000 to 4000. By making the degree of polymerization 1500 or more, the durability of the polarizing film obtained by uniaxially stretching the film can be improved. On the other hand, by making the degree of polymerization 6000 or less, the increase in manufacturing costs and the poor process passability during film making can be suppressed. It should be noted that the degree of polymerization of PVA (A) in this specification refers to the average degree of polymerization measured in accordance with the description of JIS K6726-1994.
[0077] The saponification degree of PVA (A) contained in the polarizing film of the present invention is preferably 95 mol% or more, more preferably 96 mol% or more, and further preferably 98 mol% or more, from the viewpoint of water resistance of the polarizing film obtained by uniaxially stretching the film. It should be noted that the saponification degree of PVA in this specification refers to the ratio (mol%) of the molar number of the vinyl alcohol unit relative to the total molar number of the structural unit (typically a vinyl ester unit) and the vinyl alcohol unit that can be converted into the vinyl alcohol unit (-CH2-CH(OH)-) by saponification. The saponification degree can be measured in accordance with the description of JIS K6726-1994.
[0078] The method for producing PVA (A) used in the present invention is not particularly limited. For example, a method of converting the vinyl ester unit of polyvinyl ester obtained by polymerizing vinyl ester monomers into vinyl alcohol units can be cited. The vinyl ester monomer used in the production of PVA (A) is not particularly limited, and examples thereof include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, and the like. From the viewpoint of economic efficiency, vinyl acetate is preferred.
[0079] In addition, the PVA (A) used in the present invention may be a product obtained by converting the vinyl ester units of a polyvinyl ester copolymer obtained by copolymerizing a vinyl ester monomer with other monomers copolymerizable therewith into vinyl alcohol units. Examples of other monomers copolymerizable with the vinyl ester monomer include α-olefins having 2 to 30 carbon atoms such as ethylene, propylene, 1-butene, and isobutylene; (meth)acrylic acid or its salts; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, diacetone (meth)acrylamide, (meth)acrylamidopropanesulfonic acid or its salts, (Meth)acrylamide derivatives such as (meth)acrylamidopropyldimethylamine or its salt, N-hydroxymethyl (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, and N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; vinyl cyanides such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salt, ester, or anhydride; itaconic acid or its salt, ester, or anhydride; vinyl silyl compounds such as vinyltrimethoxysilane; unsaturated sulfonic acid, etc. The above-mentioned vinyl ester copolymer may have structural units derived from one or more of the above-mentioned other monomers. The other monomers can be used by allowing the vinyl ester monomer to be preliminarily present in the reaction vessel when the vinyl ester monomer is subjected to the polymerization reaction, or by adding the monomers to the reaction vessel during the polymerization reaction. From the viewpoint of optical properties, the content of the units derived from the other monomers is preferably 10 mol% or less, more preferably 5 mol% or less, and further preferably 2 mol% or less, relative to the molar number of all structural units constituting PVA (A).
[0080] From the perspective of improving stretchability, being able to stretch at a higher temperature, reducing the occurrence of problems such as stretching breakage, and further improving the productivity of the polarizing film, the monomer that can be copolymerized with the vinyl ester monomer is preferably ethylene. When PVA (A) contains ethylene units, from the perspective of the above-mentioned stretchability, stretchable temperature, etc., the content of ethylene units is preferably 1 to 10 mol%, and more preferably 2 to 6 mol% relative to the number of moles of all structural units constituting PVA (A).
[0081] The PVA film used in the manufacture of the polarizing film of the present invention may contain a plasticizer in addition to the above-mentioned PVA (A). Preferred plasticizers include polyols, and specific examples include ethylene glycol, glycerol, propylene glycol, diethylene glycol, diglycerol, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. Furthermore, one or more of these plasticizers may be contained. Among them, glycerol is preferred from the perspective of the effect of improving stretchability.
[0082] The content of the plasticizer in the PVA film used in the manufacture of the polarizing film of the present invention is preferably in the range of 1 to 20 parts by mass, more preferably in the range of 3 to 17 parts by mass, and further preferably in the range of 5 to 15 parts by mass, relative to 100 parts by mass of PVA (A). By making the content 1 part by mass or more, the stretchability of the film is improved. On the other hand, by making the content 20 parts by mass or less, it is possible to prevent the film from becoming too soft and reducing the handling properties.
[0083] In the PVA film used to manufacture the polarizing film of the present invention, fillers, processing stabilizers such as copper compounds, weathering stabilizers, colorants, ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, other thermoplastic resins, lubricants, fragrances, defoamers, deodorants, extenders, stripping agents, mold release agents, reinforcing agents, crosslinking agents, rust inhibitors, preservatives, crystallization rate retarders, and other additives other than PVA (A) and plasticizers can be further appropriately mixed as needed. The content of other additives in the aforementioned PVA film is usually 10% by mass or less, preferably 5% by mass or less.
[0084] The swelling degree of the PVA film used in the manufacture of the polarizing film of the present invention is preferably in the range of 160 to 240%, more preferably in the range of 170 to 230%, and particularly preferably in the range of 180 to 220%. By making the swelling degree 160% or more, the crystallization can be extremely suppressed, and it can be stably stretched to a high ratio. On the other hand, by making the swelling degree 240% or less, dissolution during stretching can be suppressed, and stretching can be performed even under higher temperature conditions.
[0085] <Method for producing polarizing film>
[0086] The thickness of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited, and is generally 1 to 100 μm, preferably 5 to 60 μm, and particularly preferably 10 to 45 μm. If the aforementioned PVA film is too thin, there is a tendency for stretching fracture to occur easily during the uniaxial stretching treatment used to manufacture the polarizing film. In addition, if the aforementioned PVA film is too thick, there is a tendency for uneven stretching to occur during the uniaxial stretching treatment used to manufacture the polarizing film, and there is a tendency that the obtained polarizing film becomes thicker, making it difficult to use in thin and small devices such as smartphones and laptops.
[0087] The width of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited and can be determined according to the purpose of the manufactured polarizing film, etc. In recent years, from the perspective of promoting the large screen of liquid crystal televisions and liquid crystal displays, the width of the PVA film used in the manufacture of polarizing films is set to 3m or more, which is suitable for these uses. On the other hand, when the width of the PVA film used in the manufacture of the polarizing film is too large, it becomes difficult to uniformly perform uniaxial stretching when the polarizing film is manufactured using a practical device, so the width of the PVA film used in the manufacture of the polarizing film is preferably 10m or less.
[0088] The method for manufacturing the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited, and it is preferred to adopt a manufacturing method that makes the thickness and width of the film after film formation uniform. For example, the following film-making stock solution can be used for manufacturing: a film-making stock solution obtained by dissolving PVA (A) and, as required, further dissolving one or more of the aforementioned plasticizer, the aforementioned other additives, and the surfactant described below in a liquid medium; a film-making stock solution containing PVA (A) and, as required, further containing one or more of the plasticizer, other additives, surfactant, and liquid medium, and PVA (A) is melted. When the film-making stock solution contains at least one of a plasticizer, other additives, and a surfactant, these components are preferably uniformly mixed.
[0089] Examples of the liquid medium used in the preparation of the membrane stock solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, and diethylenetriamine. One or more of these can be used. Among them, water is preferred from the viewpoint of environmental burden and recyclability.
[0090] The volatility of the film-forming stock solution (the proportion of volatile components such as liquid medium removed by volatilization and evaporation during film-forming) also varies according to the film-forming method, film-forming conditions, etc., and is generally preferably in the range of 50 to 95% by mass, and more preferably in the range of 55 to 90% by mass. By making the volatility of the film-forming stock solution 50% or more by mass, the viscosity of the film-forming stock solution will not be too high, and filtration and degassing during the preparation of the film-forming stock solution will be smoothly performed, making it easy to manufacture a film with few foreign matter and defects. On the other hand, by making the volatility of the film-forming stock solution 95% or less by mass, the concentration of the film-forming stock solution will not be too low, and it is easy to manufacture films industrially.
[0091] The film-forming stock solution preferably contains a surfactant. By containing a surfactant, the film-forming property is improved, the occurrence of uneven film thickness is suppressed, and the film is easily peeled off from the metal roller or belt used in the film-forming. In the case of manufacturing a PVA film from a film-forming stock solution containing a surfactant, the film can contain a surfactant. The type of the above-mentioned surfactant is not particularly limited, and from the viewpoint of peelability from a metal roller or belt, an anionic surfactant or a nonionic surfactant is preferably used.
[0092] Suitable anionic surfactants include, for example, carboxylic acid type such as potassium laurate; sulfate ester type such as polyoxyethylene lauryl ether sulfate, sodium alkyl sulfate, potassium alkyl sulfate, ammonium alkyl sulfate, alkyl sulfate triethanolamine, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxypropylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, and octyl sulfate; sulfonic acid type such as sodium alkyl sulfonate, potassium alkyl sulfonate, ammonium alkyl sulfonate, alkyl sulfonate triethanolamine, sodium alkylbenzene sulfonate, disodium dodecyl diphenyl ether disulfonate, sodium alkylnaphthalene sulfonate, disodium alkyl sulfosuccinate, disodium polyoxyethylene alkyl sulfosuccinate, and dodecylbenzene sulfonate; phosphate ester type such as sodium alkyl phosphate, potassium alkyl phosphate, ammonium alkyl phosphate, alkyl phosphate triethanolamine, sodium polyoxyethylene alkyl ether phosphate, sodium polyoxypropylene alkyl ether phosphate, and sodium polyoxyethylene alkylphenyl ether phosphate.
[0093] As the nonionic surfactant, suitable ones include, for example, alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkylamine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether, etc.
[0094] These surfactants may be used alone or in combination of two or more.
[0095] When the film-forming stock solution contains a surfactant, its content is preferably in the range of 0.01 to 0.5 parts by mass, more preferably in the range of 0.02 to 0.3 parts by mass, and particularly preferably in the range of 0.05 to 0.2 parts by mass, relative to 100 parts by mass of PVA (A) contained in the film-forming stock solution. By making the content 0.01 parts by mass or more, the film-forming property and the peeling property are further improved. On the other hand, by making the content 0.5 parts by mass or less, it is possible to suppress the surfactant from seeping out on the surface of the PVA film, causing blocking and a decrease in handling properties.
[0096] As the film-making method when using the above-mentioned film-making stock solution to make the PVA film, for example, a cast film-making method, an extrusion film-making method, a wet film-making method, a gel film-making method, etc. can be cited. These film-making methods can be used only in one way, or in combination with two or more. Among these film-making methods, from the viewpoint of obtaining a PVA film for manufacturing a polarizing film with uniform thickness and width and good physical properties, a cast film-making method and an extrusion film-making method are preferably used. The PVA film obtained by film-making can be dried and heat-treated as needed.
[0097] As an example of a specific method for manufacturing the PVA film used in the manufacture of the polarizing film of the present invention, the following method can be preferably used in industry: using a T-slit die, a hopper plate, an I-die, a lip coater die, etc., the above-mentioned film-making stock solution is uniformly discharged or cast on the circumference of the first rotating and heated roller (or belt) located on the upstream side, and the volatile components are evaporated from one side of the film sprayed or cast on the circumference of the first roller (or belt) to dry, and then, it is further dried on the circumference of one or more rotating and heated rollers arranged on its downstream side, or it is further dried by passing it through a hot air drying device, and then it is wound using a winding device. Drying using a heated roller and drying using a hot air drying device can be appropriately combined. In addition, a multilayer PVA film can also be manufactured by forming a layer containing PVA (A) on one side of a substrate film composed of a single resin layer.
[0098] There is no particular limitation on the method for manufacturing the polarizing film of the present invention. A suitable manufacturing method is a method for manufacturing a polarizing film as follows: In a method for manufacturing a polarizing film that includes a dyeing treatment of dyeing a PVA film with a dichroic dye and a stretching treatment of uniaxially stretching the film, the film is immersed in an aqueous solution containing a boric acid crosslinking agent and then immersed in an aqueous solution containing a boron-containing compound (B). In addition to the aforementioned dyeing treatment and stretching treatment, the PVA film may be further subjected to swelling treatment, boric acid crosslinking treatment, fixing treatment, washing treatment, drying treatment, heat treatment, etc. as needed. There is no particular limitation on the order of the treatments, and one or more treatments may be performed simultaneously. In addition, one or more of the treatments may be performed two or more times.
[0099] The swelling treatment can be performed by immersing the PVA film in water. The temperature of the water in which the film is immersed is preferably in the range of 20 to 40°C, more preferably in the range of 22 to 38°C, and further preferably in the range of 25 to 35°C. In addition, the time of immersion in water is, for example, preferably in the range of 0.1 to 5 minutes, and more preferably in the range of 0.2 to 3 minutes. It should be noted that the water in which the film is immersed is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or a mixture of water and a hydrophilic medium.
[0100] The dyeing treatment can be carried out by contacting the PVA film with a dichroic pigment. As dichroic pigments, iodine-based pigments and dichroic dyes are generally used. The dyeing treatment can be carried out at any stage before, during, or after the stretching treatment. The dyeing treatment is generally carried out by immersing the PVA film in a solution (especially an aqueous solution) containing iodine-potassium iodide as a dyeing bath or a solution (especially an aqueous solution) containing a plurality of dichroic dyes. The concentration of iodine in the dyeing bath is preferably in the range of 0.01 to 0.5% by mass, and the concentration of potassium iodide is preferably in the range of 0.01 to 10% by mass. In addition, the temperature of the dyeing bath is preferably set to 20 to 50°C, particularly preferably 25 to 40°C. Suitable dyeing time is 0.2 to 5 minutes. In the case of using a dichroic dye, the dichroic dye is preferably an aqueous dye. In addition, the dye concentration in the dyeing bath is preferably 0.001 to 10% by mass. In addition, dyeing auxiliaries can be used as needed, and inorganic salts such as sodium sulfate, surfactants, etc. can also be used. In the case of using sodium sulfate, it is preferably 0.1 to 10% by mass. The dyeing temperature is preferably 30 to 80° C. Specific examples of dichroic dyes include CI Direct Yellow 28, CI Direct Orange 39, CI Direct Yellow 12, CI Direct Yellow 44, CI Direct Orange 26, CI Direct Orange 71, CI Direct Orange 107, CI Direct Red 2, CI Direct Red 31, CI Direct Red 79, CI Direct Red 81, CI Direct Red 247, CI Direct Green 80, and CI Direct Green 59. Dichroic dyes developed for use in the manufacture of polarizing plates are preferred.
[0101] The boric acid crosslinking treatment can be carried out by immersing the PVA film in an aqueous solution containing a boric acid crosslinking agent. By subjecting the PVA film to a boric acid crosslinking treatment, the PVA molecular chains are crosslinked, and the orientation of the PVA molecular chains is improved. As a result, the orientation of the dichroic pigment adsorbed on the PVA film is improved, so the optical properties of the resulting polarizing film are improved. From this point of view, the boric acid crosslinking treatment is more preferably carried out after the dyeing treatment and before the stretching treatment. As the aforementioned boric acid crosslinking agent, one or more of boron-containing inorganic compounds such as borate such as boric acid and borax can be used. From the perspective of easy handling, the boric acid crosslinking agent is preferably boric acid. From the perspective of being able to maintain sufficient stretchability, the concentration of the boric acid crosslinking agent in the aqueous solution containing the boric acid crosslinking agent is preferably 1 to 10% by mass, and more preferably 2 to 7% by mass. When the concentration of the boric acid crosslinking agent exceeds 10% by mass, there is a concern that crosslinking will be excessively performed and stretchability will be reduced. In addition, when the concentration of the boric acid crosslinking agent is less than 1% by mass, there is a concern that the orientation of the dichroic dye adsorbed on the PVA film is not sufficiently improved, and the polarization performance of the resulting polarizing film is not sufficiently improved. The aqueous solution containing the boric acid crosslinking agent may contain an auxiliary agent such as potassium iodide. The concentration of the boron-containing compound (B) in the aqueous solution containing the boric acid crosslinking agent is preferably 2.0% by mass or less, more preferably 0.5% by mass or less, and further preferably 0.1% by mass. It is particularly preferred that the aqueous solution does not substantially contain a boron-containing compound (B). In addition, the ratio of the concentration (mass %) of the boron-containing compound (B) in the aqueous solution containing the boric acid crosslinking agent to the concentration (mass %) of the boric acid crosslinking agent [boron-containing compound (B) / boric acid crosslinking agent] is preferably less than 1, more preferably 0.5 or less, further preferably 0.25 or less, and particularly preferably 0.1 or less. From the perspective of being able to efficiently perform boric acid crosslinking, the temperature of the aqueous solution containing the boric acid crosslinking agent is preferably 20 to 50°C, and particularly preferably 25 to 40°C.
[0102] In the manufacturing method of the present invention, the immersion of the PVA film in the aqueous solution containing the boric acid crosslinking agent can be carried out in any treatment, preferably in the boric acid crosslinking treatment. In addition, the immersion of the PVA film in the aqueous solution containing the boric acid crosslinking agent can also be carried out in multiple treatments.
[0103] In addition to the stretching treatment described later, the PVA film can also be stretched (pre-stretched) in or during the above-mentioned treatments. In this way, from the viewpoint of the optical properties of the obtained polarizing film, the total stretching ratio (the ratio obtained by multiplying the stretching ratios in each treatment) of the pre-stretching performed earlier than the stretching treatment is based on the original length of the raw PVA film before stretching, preferably 1.5 times or more, more preferably 2.0 times or more, and further preferably 2.5 times or more. On the other hand, the total stretching ratio is preferably 4.0 times or less, more preferably 3.5 times or less. As the stretching ratio in the swelling treatment, it is preferably 1.05 to 2.5 times. As the stretching ratio in the dyeing treatment, it is preferably 1.1 to 2.5 times. As the stretching ratio in the boric acid cross-linking treatment, it is preferably 1.1 to 2.5 times.
[0104] The stretching process can be carried out by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, stretching is performed in an aqueous solution. It can also be stretched in the above-mentioned dyeing bath, a boric acid aqueous solution, etc. In addition, in the case of the dry stretching method, the stretching process can be carried out at room temperature, the stretching process can be carried out while heating, and the PVA film after absorbing water can be stretched in the air. Among these, the wet stretching method is preferred, and the stretching process is more preferably carried out in an aqueous solution containing boric acid. The boric acid concentration in the boric acid aqueous solution is preferably in the range of 0.5 to 6% by mass, and more preferably in the range of 1 to 5% by mass. In addition, the boric acid aqueous solution may contain potassium iodide, and its concentration is preferably set in the range of 0.01 to 10% by mass. The stretching temperature in the stretching process is preferably 30°C or more, more preferably 40°C or more, and more preferably 50°C or more. On the other hand, the stretching temperature is preferably 90°C or less, more preferably 80°C or less, and more preferably 70°C or less. In addition, as a stretching ratio in the stretching process, it is preferably 2.0 to 4.0 times. From the viewpoint of the optical properties of the obtained polarizing film, the stretching ratio is more preferably 2.2 times or more. On the other hand, the stretching ratio is more preferably 3.5 times or less. In addition, from the viewpoint of the optical properties of the obtained polarizing film, the total stretching ratio before the fixing treatment described later is preferably 5 times or more, more preferably 5.5 times or more based on the original length of the raw material PVA film before stretching. There is no particular upper limit on the stretching ratio, and the stretching ratio is preferably 8 times or less.
[0105] The direction of uniaxial stretching in the case of stretching the long PVA film is not particularly limited, and uniaxial stretching in the direction of the long strip, transverse uniaxial stretching, and so-called oblique stretching can be adopted. From the viewpoint of obtaining a polarizing film with excellent optical properties, uniaxial stretching in the direction of the long strip is preferred. The uniaxial stretching in the direction of the long strip can be performed by using a stretching device having a plurality of rollers parallel to each other and changing the circumferential speed between the rollers. On the other hand, transverse uniaxial stretching can be performed using a tenter-type stretching machine.
[0106] When manufacturing a polarizing film, in order to make the adsorption of dichroic pigments (iodine-based pigments, etc.) on the PVA film firm, it is preferred to perform a fixing treatment after the stretching treatment. As a fixing treatment bath used in the fixing treatment, an aqueous solution containing a boron-containing compound (B) can be suitably used. In addition, as needed, boric acid, iodine compounds, metal compounds, etc. can be further added to the fixing treatment bath. The temperature of the fixing treatment bath is preferably 35°C to 80°C. On the other hand, when the temperature of the fixing treatment bath exceeds 80°C, the polarizing film is sometimes dissolved in the fixing treatment bath, or wrinkles are introduced on the polarizing film, and the polarization performance is reduced. The aforementioned temperature is more preferably below 75°C, and further preferably below 70°C. The stretching ratio in the fixing treatment is preferably 1.3 times or less, more preferably 1.2 times or less, and further preferably less than 1.1 times.
[0107] If the PVA film is immersed in an aqueous solution containing a boric acid crosslinking agent, the boron-containing compound (B) can be adsorbed on the PVA film in any process of dyeing, stretching, and fixing. From the perspective of efficiently removing unnecessary iodine-based pigments and inhibiting the breakage of the PVA film during the stretching process, it is preferred to adsorb the boron-containing compound (B) on the PVA film in the fixing process after the stretching process. The boron-containing compound (B) can be used alone or in a mixture of two or more. From the perspective of quickly performing the substitution reaction of the boron-containing compound (B) and boric acid (C) on the surface of the PVA film, the concentration of the boron-containing compound (B) in the aqueous solution used for the adsorption of the boron-containing compound (B) needs to be 1.5 to 5.0% by mass. When the above-mentioned concentration is less than 1.5% by mass, the adsorption of the boron-containing compound (B) to the surface of the PVA film slows down. The above-mentioned concentration is preferably 2.0% by mass or more, and more preferably 2.5% by mass or more. On the other hand, when the above-mentioned concentration is higher than 5.0 mass %, the boron-containing compound (B) is excessively adsorbed on the surface of the PVA film, and it is difficult to carry out the substitution reaction between the boron-containing compound (B) and the boric acid (C). In addition, there is a concern that a precipitate of the boron-containing compound (B) will be generated on the surface of the resulting polarizing film, thereby reducing the optical performance. Therefore, the concentration of the boron-containing compound (B) is preferably 4.5 mass % or less, and more preferably 4.0 mass % or less. The concentration of the aforementioned boric acid crosslinker in the aforementioned aqueous solution containing the boron-containing compound (B) is preferably 1.5 mass % or less, more preferably 1.0 mass % or less, further preferably 0.5 mass % or less, particularly preferably 0.1 mass % or less, and most preferably the aqueous solution does not substantially contain the aforementioned boric acid crosslinker. In addition, the ratio of the concentration (mass %) of the boronic acid crosslinking agent to the concentration (mass %) of the boron-containing compound (B) in the aqueous solution containing the boron-containing compound (B) [boric acid crosslinking agent / boron-containing compound (B)] is preferably less than 1, more preferably 0.5 or less, further preferably 0.25 or less, and particularly preferably 0.1 or less.
[0108] In addition, from the perspective of improving optical performance, the aqueous solution containing the boron-containing compound (B) preferably contains an auxiliary agent of iodide such as potassium iodide, and the concentration of the iodide is preferably 0.5 to 15% by mass. In addition, it is also preferred that the temperature of the aqueous solution containing the boron-containing compound (B) is 35 to 80°C. When the aforementioned temperature is less than 35°C, the replacement rate of the boron-containing compound (B) and the boric acid (C) slows down, and there is a concern that the effect of improving polarization performance becomes insufficient. The aforementioned temperature is more preferably above 40°C, and further preferably above 45°C. On the other hand, when the aforementioned temperature is too high, there is a concern that the PVA film will dissolve in the aforementioned aqueous solution, or wrinkles will be introduced into the resulting polarizing film, and the polarization performance will be reduced. Therefore, the aforementioned temperature is more preferably below 75°C, and further preferably below 70°C. The time for immersing the PVA film in the aforementioned aqueous solution is preferably 5 to 400 seconds. The aforementioned time is more preferably above 10 seconds, more preferably above 15 seconds, and particularly preferably above 20 seconds. On the other hand, the time is more preferably 350 seconds or less, further preferably 250 seconds or less, particularly preferably 150 seconds or less, and most preferably 70 seconds or less.
[0109] Examples of methods for adsorbing the boron-containing compound (B) on the PVA film include (1) a method of immersing the PVA film alone in an aqueous solution containing the boron-containing compound (B) without laminating it to a substrate film, (2) a method of laminating a substrate film on one side of the PVA film in a manner that can reduce the generation of wrinkles during the fixing process, and then immersing the resulting laminate in the aqueous solution, (3) a method of spraying an aqueous solution containing the boron-containing compound (B) on the surface of the polarizing film, and (4) a method of applying the aqueous solution on the surface of the PVA film using a roller coated with the aqueous solution, among which (1) is preferred. According to the method (1), the adsorption of the boron-containing compound (B) from the surface to the center of the PVA film is performed in the same manner on both sides, so it is preferred.
[0110] As a method for manufacturing the polarizing film of the present invention by adsorbing the boron-containing compound (B) on the PVA film during the fixing treatment, a method of sequentially performing a swelling treatment, a stretching treatment and a fixing treatment, and a method of sequentially performing a swelling treatment, a boric acid crosslinking treatment, a stretching treatment and a fixing treatment are preferred, and the latter is more preferred. After these treatments are performed, at least one treatment selected from a washing treatment, a drying treatment and a heat treatment may be further performed as required. It is preferred that after the boron-containing compound (B) is adsorbed on the PVA film, the PVA film is not immersed in an aqueous solution containing a boric acid crosslinking agent.
[0111] The washing treatment is generally carried out by immersing the film in distilled water, pure water, an aqueous solution, etc. At this time, from the viewpoint of improving optical performance, it is preferred to use an aqueous solution containing an iodide such as potassium iodide as an auxiliary agent, and the concentration of the iodide is preferably set to 0.5 to 10% by mass. In addition, the temperature of the aqueous solution in the washing treatment is generally 5 to 50°C, preferably 10 to 45°C, and more preferably 15 to 40°C. From an economic viewpoint, it is not preferred that the temperature of the aqueous solution is too low, and if the temperature of the aqueous solution is too high, the optical performance is sometimes reduced.
[0112] The drying conditions are not particularly limited, but the drying is preferably performed at a temperature in the range of 30 to 150° C., particularly preferably 50 to 130° C. Drying at a temperature in the above range makes it easy to obtain a polarizing film having excellent dimensional stability.
[0113] By performing heat treatment after drying treatment, a polarizing film with excellent dimensional stability can be further obtained. Here, heat treatment refers to a treatment in which the polarizing film having a moisture content of 5% or less after drying treatment is further heated to improve the dimensional stability of the polarizing film. The conditions of the heat treatment are not particularly limited, and the heat treatment is preferably performed in the range of 60°C to 150°C, and particularly preferably in the range of 70°C to 150°C. When the heat treatment is performed at a temperature below 60°C, the dimensional stabilization effect brought about by the heat treatment is insufficient, and when the heat treatment is performed at a temperature above 150°C, the polarizing film sometimes turns red rapidly.
[0114] The transmittance of the polarizing film of the present invention thus obtained is preferably 42.0% or more and the degree of polarization is 99.85% or more. When the transmittance of the polarizing film is less than 42.0%, there is a concern that the brightness of the resulting LCD becomes insufficient. The transmittance is more preferably 43.0% or more, and further preferably 43.5% or more. On the other hand, the transmittance is usually 48% or less. In addition, by making the degree of polarization of the polarizing film 99.85% or more, a high-quality LCD screen can be obtained. The aforementioned degree of polarization is more preferably 99.9% or more. The transmittance and degree of polarization of the polarizing film are measured by the method described in the examples described later.
[0115] The polarizing film of the present invention is usually used as a polarizing plate by laminating an optically transparent and mechanically strong protective film on both sides or one side thereof. As the protective film, a triacetate cellulose (TAC) film, a cellulose acetate-butyrate (CAB) film, an acrylic film, a polyester film, etc. are used. In addition, as an adhesive for lamination, a PVA adhesive, a UV curing adhesive, etc. can be cited.
[0116] The polarizing plate obtained in the above manner may be laminated with a phase difference film, a viewing angle enhancement film, a brightness enhancement film, etc. Alternatively, the polarizing plate may be coated with an acrylic adhesive and then laminated with a glass substrate to be used as a component of an LCD. Example
[0117] The present invention will be specifically described by the following examples, but the present invention is not limited to these examples at all. It should be noted that the evaluation methods used in the following examples and comparative examples are as follows.
[0118] <Calculation of the total boron content (T) etc. in the polarizing film>
[0119] The mass [A (g)] of the polarizing film conditioned at 23°C and 50% RH for 16 hours was measured and dissolved in 20 mL of distilled water so that the polarizing film was 0.005% by mass. The aqueous solution in which the polarizing film was dissolved was used as the measurement sample, and its mass [B (g)] was measured. The boron concentration [C (ppm)], potassium concentration [D (ppm)], and iodine concentration [E (ppm)] of the measurement sample were measured using a multi-channel ICP emission spectrometer (ICP) manufactured by Shimadzu Corporation. Then, the measured values were substituted into the following formulas (1), (2), and (3), and the calculated values were set as the total boron content (mass %), total potassium content (mass %), and total iodine content (mass %) in the polarizing film.
[0120] Total boron content in polarizing film (T, mass %)
[0121] =[(C×10 -6 ×B) / A]×100 (1)
[0122] Total potassium content in polarizing film (F, mass %)
[0123] =[(D×10 -6 ×B) / A]×100 (2)
[0124] Total iodine content in polarizing film (G, mass %)
[0125] =[(E×10 -6 ×B) / A]×100 (3)
[0126] <Calculation of Water Content (H, Mass %) in Polarizing Film>
[0127] Cut out about 0.1 g of the polarizing film conditioned at 23°C and 50% RH for 16 hours, and measure its mass [X (g)]. After drying the polarizing film in a dryer at 105°C for 16 hours, measure the mass of the polarizing film [Y (g)]. Substitute the obtained value into the following formula (4) to calculate the moisture content in the polarizing film.
[0128] Moisture content in polarizing film (H, mass %)
[0129] = (XY) / X×100 (4)
[0130] <Content of boron element derived from the boron-containing compound (B) in the polarizing film (b t )
[0131] The polarizing film was dissolved in heavy water to a concentration of 0.003% by mass, and the solution was concentrated by a rotary evaporator to a concentration of 0.15% by mass. 1 H-NMR measurement sample. 1 H-NMR (JNM-AL400: 400 MHz, manufactured by JEOL Ltd.) was measured at 80°C, and the number of accumulations was set to 256. ALICE2 (manufactured by JEOL Ltd.) was used for analysis by the following method. 1 After adjusting the phase of the H-NMR graph so that the baseline is smooth, the average point number is set to 20 and the baseline is automatically corrected. Next, the peak of heavy water, which is the measurement solvent, is automatically set to 4.65 ppm as a reference. Figure 2 In this way, the hydrogen peak of the hydrocarbon group contained in the boron-containing compound (B) is integrated to obtain its peak area (area I). At this time, the area (area J) obtained by adding the areas of the hydrogen peaks of the hydrocarbon groups contained in the boron-containing compound (B) that do not overlap with the hydrogen peaks derived from PVA is used as the basis for the peak area, and the number of hydrogens of the corresponding hydrocarbon groups of the boron-containing compound (B) is set in a manner that is the same as the value of area J. Next, the hydrogen peak in the range of 1.6 to 2.4 ppm is regarded as the sum of the hydrogen peak of the methylene group derived from PVA and the hydrogen peak of the hydrocarbon group contained in the boron-containing compound (B) that overlaps with the hydrogen peak of the methylene group derived from PVA, and the peak area (area K) is obtained. Thereafter, the number of hydrogens of the hydrocarbon group of the boron-containing compound (B) that overlaps with the hydrogen peak of the methylene group derived from PVA is subtracted from the area K to calculate the area L. The values obtained by these methods are substituted into the following formula (5) to calculate the content (M, mass parts) of the organic group derived from the boron-containing compound (B) relative to 100 parts by mass of PVA (A). In addition, the values are substituted into the following formula (6) to obtain the boron content (N, mass parts) derived from the boron-containing compound (B) relative to 100 mass parts of PVA (A). It should be noted that O in the following formulas (5) and (6) is the number of hydrogen atoms in the hydrocarbon group contained in the boron-containing compound (B) that does not overlap with the peak of PVA, P is the number of boron atoms per molecule of the boron-containing compound (B), and Q is the formula weight of the organic group of the boron-containing compound (B). Then, the calculated values are substituted into formula (7) to calculate the boron content (b) derived from the boron-containing compound (B) in the polarizing film. t , mass %). It should be noted that formulas (5), (6), and (7) are used when unmodified PVA is used. When modified PVA is used as a raw material, formulas (5), (6), and (7) need to be appropriately modified.
[0132] Content of organic groups derived from the boron-containing compound (B) relative to 100 parts by mass of PVA (A) (M, parts by mass)
[0133] ={(Area J / O) / (Area L / 2)}×(Q / 44.0526)×100 (5)
[0134] Boron content derived from the boron-containing compound (B) relative to 100 parts by mass of PVA (A) (N, parts by mass)
[0135] ={(Area J / O) / (Area L / 2)}×(10.811×P / 44.0526)×100 (6)
[0136] The boron content (b t ,quality%)
[0137] =N×1 / (100+M)×(100-TFGH) (7)
[0138] In the formula, 10.811 is the atomic weight of boron, and 44.0526 is the molecular weight per 1 mol of repeating unit of unmodified PVA. Figure 2 of 1 The H-NMR chart is a chart obtained by measuring the polarizing film of Example 1.
[0139] <Boron element concentration(b o ), boron concentration (b i ), boron concentration (c o ) and boron concentration (c i ) is calculated >
[0140] The concentration of boron element derived from the boron-containing compound (B) in the polarizing film was measured using an X-ray photoelectron spectrometer (GCIB-XPS) with a gas cluster ion beam gun (Albuck Fiber Co., Ltd.: PHI5000 VersaProbe II). The polarizing film was humidified at about 23°C / 40%RH for more than 16 hours. The ion source was Ar2500. +, accelerating voltage 10keV, current value 30nA, neutralized, and sputtered in the range of 1mm×1mm, and X-ray photoelectron spectroscopy (XPS measurement) was performed. XPS measurement was carried out under the settings of using monochromatic Al as the X-ray source, 200μm in X-ray spot diameter, 15kV and 50W in X-ray output, and 5 detection elements were selected: carbon, boron, oxygen, iodine and potassium. It should be noted that when using dichroic dyes in dichroic pigments, elements such as nitrogen and sulfur contained in the dichroic dyes also need to be appropriately selected from the detection elements. Next, the analysis software "MultiPak" (manufactured by Albuck Fiber Co., Ltd.) was used to calculate the boron concentration (a, atomic %) at each depth of the polarizing film based on the binding energy of CC and CH bonds, i.e. 284.8eV. Then, for the XPS spectrum at each depth, the binding energy of boron from boric acid (C) and the binding energy of boron from boron-containing compound (B) are appropriately set, and the table calculation software "Microsoft 2010" (made by Microsoft Corporation) is used, and the Pseudo-Voigt function is used to perform peak separation by the least square method. It should be noted that the linear function calculated by the average value of the intensity of the XPS spectrum from 187 to 189 eV and the average value of the XPS spectrum from 195 to 197 is used as a baseline. In this way, the ratio (b, %) of the peak area of boron from boron-containing compound (B) to the total peak area of boron from boric acid (C) and the peak area of boron from boron-containing compound (B) is calculated, and the boron element concentration from boron-containing compound (B) at each depth and the boron element concentration from boric acid (C) at each depth are calculated by substituting the following calculation formula (8).
[0141] Concentration of boron element from boron-containing compound (B) (atomic %)
[0142] =a×b×10 -2 (8)
[0143] Concentration of boron from boric acid (C) (atomic %)
[0144] =a×(100-b)×10 -2 (9)
[0145] It should be noted that the binding energy of boron from the boron-containing compound (B) varies depending on the structure of the compound. Therefore, it is necessary to appropriately set the above binding energy according to the type of the boron-containing compound (B). For example, in the case where the boron-containing compound (B) is n-propylboric acid, it is around 191.5 eV. In addition, when the Pseudo-Voigt function is used to perform peak separation by the least squares method, the Lorentz function ratio of boric acid is set to 0.241, 2 1 / 2×σ is set to 0.916. It should be noted that the Lorentz function ratio and half peak width of the boron-containing compound (B) also vary depending on the structure of the compound. Therefore, the Lorentz function ratio and 2σ need to be appropriately set according to the type of the compound. 1 / 2 ×σ. In the case where the boron-containing compound (B) is n-propylboric acid, the Lorentz function ratio is set to 0.000, 2 1 / 2 ×σ is set to 0.769.
[0146] By this method, the boron concentration (atomic %) derived from the boron-containing compound (B) and the boron concentration (atomic %) derived from the boric acid (C) at each depth from one surface to the center of the polarizing film are calculated. Specifically, the etching range is set so that the etching rate is about 16 to 26 nm / min, and a total of 14 measurements are performed while etching from one surface to the center of the polarizing film, and the boron concentration (atomic %) derived from the boron-containing compound (B) and the boron concentration (atomic %) derived from the boric acid (C) are calculated for each measurement, that is, at each depth. Moreover, the same measurement is performed from the other surface of the polarizing film, and the boron concentration (atomic %) derived from the boron-containing compound (B) and the boron concentration (atomic %) derived from the boric acid (C) at each depth are calculated. Then, the average value of the boron concentration derived from the boron-containing compound (B) calculated in the range from the surface of the polarizing film to the inside to 7.5% relative to the total thickness is set as the boron concentration (atomic %) derived from the boron compound (B). o , atomic %), and the average value of the boron element concentration (atomic %) derived from the boric acid (C) calculated in this range is defined as the boron element concentration (atomic %) derived from the boric acid (C). o ,atom%).
[0147] The average value of the boron element concentration derived from the boron-containing compound (B) calculated from the center of the polarizing film to the outside to 7.5% of the total thickness is defined as the boron element concentration derived from the boron-containing compound (B) (b i , atomic %), and the average value of the boron element concentration derived from the boric acid (C) calculated in this range is defined as the boron element concentration derived from the boric acid (C) (c i , atomic %). It should be noted that, in order to reduce the error, the measured value of the outermost surface where sputtering was not performed was excluded, and the average concentration (c o ) and (b o ).
[0148] <Optical properties of polarizing films>
[0149] From the center of the width and length directions of the polarizing film, a rectangular sample of 4 cm in the length direction and 2 cm in the width direction of the polarizing film was collected, and the parallel transmittance and the orthogonal Nicol transmittance of the polarizing film were measured using a spectrophotometer V-7100 (manufactured by JASCO Corporation) with an integrating sphere and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan-Taylor polarizer. Here, the measurement wavelength range is set to 380nm to 780nm, and for the vibration direction of the polarized light incident on the polarizing film through the Glan-Taylor polarizer, the transmittance in the case of being parallel to the transmission axis of the polarizing film is recorded as the parallel transmittance, and the case of being perpendicular to the transmission axis of the polarizing film is recorded as the orthogonal Nicol transmittance. Then, using the "Polarizing Film Evaluation Program" (manufactured by JASCO Corporation), as in accordance with JIS Z 8722 (Method for measuring object color), the aforementioned parallel transmittance and orthogonal Nicol transmittance are used to perform visual sensitivity correction in the visible light region of C light source and 2° field of view, and the single body transmittance and polarization degree of the polarizing film are calculated, and these two values are obtained as the optical properties of the polarizing film.
[0150] <Swelling degree of PVA film>
[0151] The PVA film was cut into 5 cm × 10 cm pieces and immersed in 1000 mL of distilled water at 30°C for 30 minutes. Afterwards, the PVA film was taken out, the water on the surface of the PVA film was wiped with filter paper, and the mass of the PVA film after immersion [R (g)] was measured. Afterwards, the PVA film was dried in a dryer at 105°C for 16 hours, and the mass of the PVA film after drying [S (g)] was measured. The swelling degree of the PVA film was calculated by substituting the value into the following formula (10).
[0152] Swelling degree (%) = (R / S) × 100 (10)
[0153] [Example 1]
[0154] A PVA aqueous solution containing 100 parts by mass of PVA (99.9% saponification degree, 2400 degree of polymerization), 10 parts by mass of glycerol as a plasticizer, and 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, and having a PVA content of 10% by mass, was prepared. The PVA aqueous solution was dried on a metal roll at 80° C., and the obtained film was heat-treated in a hot air dryer at a temperature of (120° C.) for 10 minutes to obtain a PVA film having a thickness of 30 μm and a swelling degree of 200%.
[0155] From the central part of the width direction of the obtained PVA film, a sample of 5 cm in width and 9 cm in length is cut out in a manner that a range of 5 cm in width and 5 cm in length can be uniaxially stretched. The sample is immersed in pure water at 30°C for 30 seconds, and uniaxially stretched to 1.1 times along the length direction for swelling treatment. Then, it is immersed in an aqueous solution (dyeing treatment bath) at 30°C containing 0.035% by mass of iodine and 3.5% by mass of potassium iodide for 60 seconds, and uniaxially stretched to 2.2 times (2.4 times as a whole) along the length direction to adsorb iodine. Then, it is immersed in an aqueous solution (boric acid cross-linking treatment bath) at 30°C containing boric acid at a ratio of 3.0% by mass and potassium iodide at a ratio of 3% by mass, and uniaxially stretched to 1.2 times (2.7 times as a whole) along the length direction. Furthermore, the film was immersed in a 60°C aqueous solution (stretching treatment bath) containing 4.0% by mass of boric acid and 6% by mass of potassium iodide, and uniaxially stretched to 6.0 times as a whole along the length direction. After the stretching treatment, the film was immersed in a 50°C aqueous solution (fixing treatment bath) containing 3.0% by mass of n-propyl boric acid as a boron-containing compound (B) and 3.5% by mass of potassium iodide for 30 seconds. During the fixing treatment, the PVA film was not stretched (stretching ratio 1.0 times). Finally, it was dried at 60°C for 240 seconds to produce a polarizing film (thickness 13μm).
[0156] The total boron content, potassium content, and iodine content of the obtained polarizing film were measured, and the results were 4.3 mass%, 1.0 mass%, and 5.0 mass%, respectively. Next, the moisture content of the polarizing film was calculated, and the result was 10.0 mass%. In addition, the polarizing film was measured. 1 H-NMR was analyzed and the result showed that the hydrogen peak of n-propylboric acid that did not overlap with the hydrogen peak derived from PVA appeared at 1.1-1.3 ppm, so the peak area (area J) was set to 5. Next, the peak area (area K) of the hydrogen of the methylene group of PVA that appeared in the range of 1.6-2.4 ppm was calculated. The hydrogen peak of the methylene group of PVA overlapped with the hydrogen peak of the C2 hydrocarbon group of n-propylboric acid, so the number of hydrogen atoms of the C2 hydrocarbon group of n-propylboric acid, 2, was subtracted from the area K to obtain the area L. Substituting these values into the above-mentioned formulas (5), (6), and (7), the result showed that the content of boron derived from the boron-containing compound (B) in the polarizing film was 0.7% by mass. The XPS spectrum of the polarizing film was measured and analyzed, and the result showed that the boron concentration (b) derived from the boron-containing compound (B) in the range from the surface of the polarizing film to the inside to 7.5% relative to the total thickness (surface portion) was 0.7%. o ) is 3.1 atomic %, and the concentration of boron element (c o) is 4.6 atomic %. In addition, the concentration of boron element (b) derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside to 7.5% of the total thickness (central portion) is i ) is 1.1 atomic %, and the boron element concentration (c i ) is 5.7 atomic %.
[0157] The optical properties of the polarizing film were evaluated by the above-mentioned method. As a result, the single body transmittance at a polarization degree of 99.9% was 44.85%.
[0158] [Examples 2, 3, Comparative Examples 1 to 5]
[0159] A polarizing film was prepared in the same manner as in Example 1, and various measurements and evaluations were performed, except that the composition, temperature, and immersion time of the fixing treatment bath were changed as shown in Table 1. 1 In the H-NMR measurement, the boron-containing compound (B) could not be detected when the integration number was 256, so the integration number was changed to 4096.
[0160] [Comparative Example 6]
[0161] Comparative Example 6 is an example of a polarizing film that does not contain the boron-containing compound (B). A polarizing film was prepared in the same manner as in Example 1, and various measurements and evaluations were performed, except that an aqueous solution containing 2% by mass of potassium iodide (temperature 30° C.) was used as a fixing treatment bath, and the immersion time in the fixing treatment bath was changed to 20 seconds.
[0162] [Comparative Example 7]
[0163] Comparative Example 7 is an example of a polarizing film that does not contain the boron-containing compound (B). A polarizing film was prepared in the same manner as in Example 1, and various measurements and evaluations were performed, except that an aqueous solution containing 2% by mass of potassium iodide (temperature 30° C.) was used as a fixing treatment bath, and the immersion time in the fixing treatment bath was changed to 5 seconds.
[0164] It should be noted that in Examples 2 to 3 and Comparative Examples 1 to 7, the film was immersed in an aqueous solution (dyeing treatment bath) (temperature 30°C) containing 100 parts by mass of potassium iodide relative to 1 part by mass of iodine for 60 seconds, and uniaxially stretched to 2.2 times (2.4 times as a whole) in the longitudinal direction in the same manner as in Example 1, so that iodine was adsorbed. At this time, the iodine concentration and potassium iodide concentration of the dyeing treatment bath were adjusted so that the polarization degree of the polarizing film after drying was 99.9%. In addition, in any of Examples 1 to 3 and Comparative Examples 1 to 7, the surfaces on both sides of the polarizing film were measured and evaluated, and the results were the same. The reason for the same results on the surfaces on both sides of the polarizing film is presumed to be because the adsorption of the boron-containing compound (B) from the surface to the center of the PVA film is carried out in the same manner on both sides during the fixing process.
[0165]
[0166] As shown in Table 1, the polarizing films of Examples 1 to 3 of the present invention have high polarization performance and high single-body transmittance, and can meet the recent demand for higher definition electronic devices.
[0167] Explanation of symbols
[0168] 1 Surface
[0169] 2 Surface
[0170] 3 Central
[0171] 4 Central
[0172] 5 Hydrogen peak from heavy water used as the measurement solvent
[0173] 6 Hydrogen peak from the methine group of PVA
[0174] 7 Hydrogen peak from the methylene group of PVA
[0175] 8 Hydrogen peaks originating from hydrocarbon groups contained in the boron-containing compound (B) overlapping with the hydrogen peaks originating from PVA
[0176] 9 Hydrogen peak derived from hydrocarbon groups contained in the boron-containing compound (B) that does not overlap with the hydrogen peak derived from PVA
[0177] t o ,t i ,t t thickness
Claims
1. A polarizing film comprising polyvinyl alcohol (A), a boron-containing compound (B) selected from the group consisting of monoboric acid represented by the following formula (I) and a compound that can be converted into the monoboric acid in the presence of water, and boric acid (C), wherein: Boron content from the boron-containing compound (B) t is 0.3 to 2.0% by mass, the total boron content T is 3.0 to 7.0% by mass, and b t Ratio b relative to T t / T is 0.10~0.30, The boron element concentration b derived from the boron-containing compound (B) in the range from at least one surface to the inside to 7.5% relative to the entire thickness o 2.2 to 10.0 atomic % The boron element concentration b derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside to 7.5% with respect to the total thickness is i The boron concentration c derived from the boric acid (C) is 0.5 to 2.0 atomic %. i 3.5 to 8.0 atomic % [Chemical Formula 1] In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 It is connected to the boronic acid group by a boron-carbon bond.
2. The polarizing film according to claim 1, wherein The boron element concentration b derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside to 7.5% with respect to the total thickness is i The boron concentration c derived from the boric acid (C) is 0.8 to 1.8 atomic %. i 4.0 to 7.0 atomic %.
3. The polarizing film according to claim 1 or 2, wherein: The boron element concentration b derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside to 7.5% with respect to the total thickness is i Relative to the boron concentration c derived from boric acid (C) i The ratio b i / c i It is 0.01~0.
25.
4. The polarizing film according to claim 1 or 2, wherein: The boron element concentration c derived from the boric acid (C) in the range from at least one surface of the polarizing film to the inner side to 7.5% with respect to the entire thickness o It is 3.3 to 7.8 atomic %.
5. The polarizing film according to claim 1 or 2, wherein: The boron element concentration b derived from the boron-containing compound (B) in the range from at least one surface of the polarizing film to the inner side to 7.5% with respect to the entire thickness is o The concentration of boron element derived from the boron-containing compound (B) in the range from the center of the polarizing film to the outside to 7.5% with respect to the total thickness is b i high.
6. The polarizing film according to claim 1 or 2, wherein: The boron element concentration c derived from the boric acid (C) in the range from at least one surface of the polarizing film to the inner side to 7.5% with respect to the entire thickness o The concentration c of the boron element derived from the boric acid (C) in the range from the center of the polarizing film to the outside to 7.5% with respect to the total thickness is i Low.
7. The polarizing film according to claim 1 or 2, wherein: R 1 It is a saturated aliphatic group.
8. The polarizing film according to claim 1 or 2, wherein: R 1 It is a straight-chain aliphatic hydrocarbon group.
9. The polarizing film according to claim 1 or 2, wherein: R 1 The number of carbon atoms is 2 to 5.
10. The polarizing film according to claim 1 or 2, wherein: The transmittance when the polarization degree is 99.9% or more is 42% or more.
11. The method for producing a polarizing film according to any one of claims 1 to 10, comprising dyeing a polyvinyl alcohol film with a dichroic dye and stretching the film uniaxially, in, The film is subjected to a boric acid crosslinking treatment by immersing the film in an aqueous solution containing a boric acid crosslinking agent, and then immersed in an aqueous solution containing 1.5 to 5.0 mass % of a boron-containing compound (B) at a temperature of 35 to 80° C., The boric acid cross-linking treatment is performed after the dyeing treatment and before the stretching treatment.